FATHERHOOD OF JAVANESE LOW-MIDDLE CLASS - M. Wahib Sahie (Psychosophia: Journal of Psychology, Religion, and Humanity, 2020)
This study aims to explore the masculine identity of the fatherhood of Javanese men and to understand its psychological dynamics through ‘the experience of being a father’. Therefore, the researcher applied hermeneutic-phenomenology study that which is digging beneath the configuration inside and also construct the gender structure. Also, in this study the subject of researchers came from Java residing in Jomblang Karang Bendo and in this study are those who are in the category of low-middle class. The findings in this study explain that fatherhood is constructed through discourse which is a requirement of the engendered fatherhood. Furthermore, fatherhood is a figure needed in the family (wife and children).